Solidstate advertisement display / Mohd Zaimi Mohd Yusof and Mohd Ridwan Hakimi Ahmad - Mohd Yusof, Mohd Zaimi (2004)
We are interested about SOLIDSTATE ADVERTISEMENT DISPLAY that we choose from ours discussion with our supervisor and researched it. These projects are made with multicolor semitransparent plastic sheets and each of the letters is separated by black opaque sheets. Each letters displayed one by one and finally all letters of ‘WELCOME’ or any other words are displayed. The circuit automatically reset after the last letter. Then again, the circuit begins to function by displayed the letters. This process is repeated endlessly. This circuit can use to attract customer or anybody to come to their shop, office or house. It also can make their business to get more profit. This circuit also can make their shop interesting. The circuits use 9v for the supply. All the components are available at any electronic shop. The circuit easy to do and it not expensive.